2003
DOI: 10.1046/j.1529-8019.2003.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary therapy for atopic eczema and other allergic skin diseases

Abstract: Atopic eczema is one of the most common chronic inflammatory skin diseases, with a prevalence of at least 10% in children and 0.5-1% in adults. The disease shows a drastically increasing tendency. This article provides an overview of the pathophysiology, pathomechanisms, prevention, and treatment of atopic eczema. We present a therapeutic concept that integrates all aspects of the complex pathophysiology that is a prerequisite for individualized and successful treatment. This is based on intervention in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 77 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…On the other hand, 36% of participants answered that Chinese herbal therapies can cure AD and are safe because they do not contain corticosteroid. However, Chinese herbal therapies may contain toxic substances such as heavy metals and drug components such as glucocorticosteroid, diazepam, phenylbutazone, paracetamol and thiamine22. They are not safe and may even be harmful, because their composition is unclear and they may have corticosteroid-like actions in some cases22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 36% of participants answered that Chinese herbal therapies can cure AD and are safe because they do not contain corticosteroid. However, Chinese herbal therapies may contain toxic substances such as heavy metals and drug components such as glucocorticosteroid, diazepam, phenylbutazone, paracetamol and thiamine22. They are not safe and may even be harmful, because their composition is unclear and they may have corticosteroid-like actions in some cases22.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chinese herbal therapies may contain toxic substances such as heavy metals and drug components such as glucocorticosteroid, diazepam, phenylbutazone, paracetamol and thiamine22. They are not safe and may even be harmful, because their composition is unclear and they may have corticosteroid-like actions in some cases22. Presently, questions related to skin care and environment management related to dietary restrictions, emollient use, bathing and breast feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chronic use of stronger steroids may lead to a rebound phenomenon, steroid dermatitis, and rosacea-like lesions (17). Traditional herbs is an alternative therapy that can be used in the treatment of dermatologic disorders (18,19). Previous studies have shown that herbal therapy with oriental medicine may be beneficial for the treatment of patients with atopic dermatitis (20).…”
Section: Introductionmentioning
confidence: 99%
“…There is no convincing evidence that acupuncture is an efficacious treatment in skin diseases [99]. Case reports of homeopathy applied successfully in dermatological conditions [100] are not supported by empirical evidence [101].…”
Section: Other Cam Therapies In Skin Diseasesmentioning
confidence: 99%